Ideology (translation. a transdisciplinary journal, 2022)
The “need to think ideologically about translation research” is a call I made in another paper (Cheung 2002). I would like to reiterate it here. To think ideologically about translation research does not mean that we treat everything as ideologically suspect. It does mean, however, that we accept ideological leanings/bias/convictions as an epistemological fact, as something that is built into our attempts to make sense of things.